ECONOMETRIC MODELING AND FORECASTING OF GREEN TOURISM DEVELOPMENT IN UZBEKISTAN (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This study focuses on the econometric modeling and forecasting of green tourism development in Uzbekistan, a sector increasingly vital for sustainable economic growth. Utilizing time-series data from 2010 to 2024, encompassing indicators such as tourist arrivals, environmental sustainability metrics, and investment in eco-friendly infrastructure, we construct a Vector Autoregressive (VAR) model to analyze the dynamic relationships among these variables. The model incorporates exogenous factors like government policies and global environmental trends to enhance predictive accuracy. Results indicate that green tourism growth is positively influenced by investments in renewable energy and protected natural areas, though constrained by infrastructural bottlenecks. Forecasting scenarios for 2025–2030 project a moderate increase in green tourism under current policies, with potential for accelerated growth through enhanced eco-certification and digital marketing strategies. The findings provide actionable insights for policymakers aiming to balance economic development with environmental preservation in Uzbekistan’s tourism sector.